UNDERSTANDING SUSTAINABLE ACCOMMODATION CHOICES: A SEGMENTATION ANALYSIS USING EXTENDED TPB - Marina Haro-Aragu; Josefa Garcia-Mestanza; Lidia Caballero-Galeote (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2025)
The integration of sustainable practices is paramount for fostering responsibility and sustainability in pivotal sectors such as tourism. This study aims to analyse the intention to book into any type of sustainable accommodations by employing the Theory of Planned Behaviour (TPB) extended with price sensitivity. This research applies FIMIX-PLS to segment the sample based on the TPB framework, which involves the analysis of respondents' attitudes, subjective norms, perceived behavioural control, and price sensitivity concerning sustainable accommodation. The results highlight that attitude is the main predictor of booking intention, followed by price sensitivity. The segmentation analysis reveals four distinct groups composed solely of women, which represents an innovation in terms of perspectives on the role of gender in sustainable tourism behaviour. In this sense, understanding gender divergences in sustainable tourism can inform more inclusive and effective sustainability policies that promote wider societal adoption of sustainable practices. Future research could expand the sample size and explore additional variables that may influence sustainable booking intentions. The results offer practical implications for business management, emphasizing the need for targeted marketing strategies that consider gender-based differences in sustainability perceptions.